The Effect of Baby Spa on Body Weight Changes in Babies Aged 3-6 Months - Fitriani; Sri Wahyuningsih; Agustina Widayati; Sunanto (Health and Technology Journal (HTechJ), 2023)
Infants aged 0-6 months are the most vulnerable to growth disorders. One way to increase a baby's weight is through baby SPA. This study aimed to determine the effect of infant SPA on weight changes in infants aged 3-6 months. This study used a quasi-experimental design with a control group pre-post test design approach. The population in this study were all infants aged 3-6 months at Ain Hartoko SPA, Tempeh District, Lumajang Regency, in July 2022. As many as 42 infants were divided into two groups, the experimental and the control groups, using the accidental sampling technique. The results showed that the baby's weight gain in the experimental group was mostly classified as overweight (56.3%), while in the control group, most were normal (62.5%). The Wilcoxon test results for the p-value for the experimental and control groups were both 0.000, so they experienced an increase in body weight after two weeks. The Mann-Whitney test results obtained p-value=0.045 <0.05, so infant SPA affects weight changes in infants aged 3-6 months. Health workers are expected to conduct counseling about infant SPA in collaboration with Toddler Posyandu cadres in the village to overcome failure to thrive in toddlers.